(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Flax has been of great importance in Latvia for a long time. It is a sources of raw materials of valuable products – fibre and oil for national economy. The total content of oil and fatty acids in the 42 sorts of linseed was determined. The use of pre-seeding biostimulators (microorganism metabolite – Germin, microelements copper, zinc and boron) resulted in positive changes in total contents of an oil and unsaturated fatty acids (linoleic and linolenic) in the linseed of following generation was determined. Under the influence of biostimulators an augmentation of the yield of flax straw for 8–21% in comparison with control was observed. The yield of linseed increased for 6–28%, correspondingly.